A mathematical model and a heuristic approach for train seat scheduling to minimize dwell time. (October 2021) - Ayaz, Halil Ibrahim; Kamisli Ozturk, Zehra
Highlights: This paper proposes a new heuristic approach and a mathmetical model for the train seat scheduling problem. In the proposed method, there are two aims, such as minimizing dwell times and provide a proper schedule. The proposed method was compared with a mathematical model. Abstract: Rail is fast becoming a key instrument in the transportation of passengers and cargo. Especially, high-speed trains are gaining more importance in recent decades to passenger transportation. However, some problem arises for passenger transportation due to passengers' improper scheduling or trains' dwell time. These problems negatively affect customer satisfaction and revenue management. Although there are many studies about customer satisfaction and revenue management for transportation, a small part of these studies are illustrated in railways. In this study, the train seat scheduling problem is converted into a parallel machine scheduling problem and the problem is redefined considering the scheduling perspective. Then, a mathematical model and a heuristic algorithm are developed considering the mentioned problems. The proposed algorithm provides a feasible scheduling plan in a reasonable time scale, considering dwell times and a proper scheduling plan. Both methods are used to solve the problem, and comparative results are presented.